Teacher Learning in Scaffolding Children’s Collaborative Dialogue in a Chinese Elementary School - Jingjing Sun (孙晶晶); Jie Zhang (张洁); Hong Li (李虹) (ECNU Review of Education)
Purpose: Dialogic pedagogies that provide students with frequent opportunities to talk have been shown to help students develop essential 21st-century skills. Many Chinese teachers, however, lack confidence and experiences in shifting from teacher-centered pedagogical practices to such student-centered practices. This study examined Chinese elementary school teachers’ reflections on learning to facilitate small-group collaborative reasoning (CR) discussions in their classrooms. Design/Approach/Methods: Two fourth-grade teachers in a public school in Beijing, China, participated in the study, where they participated in seven semi-structured debriefing interviews and wrote 13 reflective journals. Thematic analysis of the debriefing interviews and journals was carried out to understand the teachers’ learning progress. Findings: The results showed that although the teachers encountered major challenges, such as a drastic shift in their roles, the intense cognitive demands of scaffolding, and the emotional stress of handling the uncertainties of CR discussions, they also made noteworthy progress while learning to facilitate CR discussions. The teachers’ achievement goal orientations seem to have played a major role in how they responded to the challenges and whether they made progress. Originality/Value: This study reveals insights into the challenges and progress that the teachers experienced when learning to use a discussion-based teaching approach. It sheds light on the motivational mechanism of teacher learning and provides guidance on how to support Chinese teachers through the use of small-group collaborative discussions.